2021
DOI: 10.1002/cam4.3891
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on chemotherapy de‐escalation in breast cancer

Abstract: BackgroundGiven excellent survival outcomes in breast cancer, there is interest in de‐escalating the amount of chemotherapy delivered to patients. This approach may be of even greater importance in the setting of the COVID‐19 pandemic.MethodsThis concurrent mixed methods study included (1) interviews with patients and patient advocates and (2) a cross‐sectional survey of women with breast cancer served by a charitable nonprofit organization. Questions evaluated interest in de‐escalation trial participation, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Indeed, some previous reports showed that the term 'de-escalation' may not be the most preferred term by some patients, who may feel that they will receive substandard treatments. 53,54 Patients can hold high expectations on adjuvant therapy and may prefer chemotherapy, albeit providing small benefits, when the communication of the absolute benefit is imperfect or the benefits of alternative approaches are not comprehensively articulated. [55][56][57] Fear surrounding recurrence has been reported as a major barrier to participation in clinical trials of treatment modulation.…”
Section: Clinical and Decisional Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, some previous reports showed that the term 'de-escalation' may not be the most preferred term by some patients, who may feel that they will receive substandard treatments. 53,54 Patients can hold high expectations on adjuvant therapy and may prefer chemotherapy, albeit providing small benefits, when the communication of the absolute benefit is imperfect or the benefits of alternative approaches are not comprehensively articulated. [55][56][57] Fear surrounding recurrence has been reported as a major barrier to participation in clinical trials of treatment modulation.…”
Section: Clinical and Decisional Issuesmentioning
confidence: 99%
“…[55][56][57] Fear surrounding recurrence has been reported as a major barrier to participation in clinical trials of treatment modulation. 53 At the same time, the reduction of physical and financial toxicities and the description of a positive impact on daily life were attractive aspects of treatment with reduced intensity. 53 Importantly, patients' views on de-escalated treatment regimens may vary according to individual values and priorities.…”
Section: Clinical and Decisional Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our cross-sectional survey of women with breast cancer found that 58% of respondents would have been interested in participating in a clinical trial testing less than standard chemotherapy, the primary motivating factor being to avoid physical toxicity [6]. Remaining survey respondents expressed unwillingness to participate in such a trial, primarily due to fear of recurrence.…”
Section: Introductionmentioning
confidence: 97%